2010
DOI: 10.1021/jp107269q
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Pathways of Clathrate Hydrates: Effect of Guest Size and Solubility

Abstract: Understanding the microscopic mechanism of nucleation of clathrate hydrates is important for their use in hydrogen storage, CO(2) sequestration, storage and transport of natural gas, and the prevention of the formation of hydrate plugs in oil and gas pipelines. These applications involve hydrate guests of varied sizes and solubility in water that form different hydrate crystal structures. Nevertheless, molecular studies of the mechanism of nucleation of hydrates have focused on the single class of small hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
236
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(258 citation statements)
references
References 54 publications
18
236
0
Order By: Relevance
“…Modeling shows that natural gas clathrate hydrates form along a pathway wherein dissolved guest molecules (i.e., natural gas) quasi-equilibrate with an enriched guest separated phase (i.e., the nuclei). This phase changes irreversibly to become a structured natural gas clathrate hydrate (Jacobson et al, 2010) This modeling is in contrast to the labile cluster model where cages spontaneously enclathrate solvated guest molecules and assemble to form the hydrates (Sloan and Fleyfel, 1991), but it is similar to the model of Radhakrishnan and Trout (Radhakrishnan and Trout, 2002). Taking the most recent modeling work of Jacobson and coworkers as highly accurate (Jacobson et al, 2010), one way to inhibit natural gas clathrate hydrate would be to change the surface energy at the interface of the nuclei and the bulk solution, such that the surface area (along with the volume) of the nuclei decreases to disappearance.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Modeling shows that natural gas clathrate hydrates form along a pathway wherein dissolved guest molecules (i.e., natural gas) quasi-equilibrate with an enriched guest separated phase (i.e., the nuclei). This phase changes irreversibly to become a structured natural gas clathrate hydrate (Jacobson et al, 2010) This modeling is in contrast to the labile cluster model where cages spontaneously enclathrate solvated guest molecules and assemble to form the hydrates (Sloan and Fleyfel, 1991), but it is similar to the model of Radhakrishnan and Trout (Radhakrishnan and Trout, 2002). Taking the most recent modeling work of Jacobson and coworkers as highly accurate (Jacobson et al, 2010), one way to inhibit natural gas clathrate hydrate would be to change the surface energy at the interface of the nuclei and the bulk solution, such that the surface area (along with the volume) of the nuclei decreases to disappearance.…”
Section: Introductionmentioning
confidence: 84%
“…This phase changes irreversibly to become a structured natural gas clathrate hydrate (Jacobson et al, 2010) This modeling is in contrast to the labile cluster model where cages spontaneously enclathrate solvated guest molecules and assemble to form the hydrates (Sloan and Fleyfel, 1991), but it is similar to the model of Radhakrishnan and Trout (Radhakrishnan and Trout, 2002). Taking the most recent modeling work of Jacobson and coworkers as highly accurate (Jacobson et al, 2010), one way to inhibit natural gas clathrate hydrate would be to change the surface energy at the interface of the nuclei and the bulk solution, such that the surface area (along with the volume) of the nuclei decreases to disappearance. Another possible way to inhibit the natural gas clathrate hydrates would be to add into the system a polymer attracted to the nuclei core (i.e., a polymer more hydrophobic than the bulk solution) to disrupt the structuring process (Rodger, 2011).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…3B. Previous work has indicated that gas hydrate nucleation proceeds with the formation of solvent-separated guest molecules and water molecule rearrangement to yield cages (33). Therefore, the early reductions in the MSD values of the water molecules, without commensurate changes to the tetrahedral ordering of the aqueous phase, may be indicative of early stage ordering of guest molecules in the aqueous phase.…”
mentioning
confidence: 95%
“…MD gREM simulations, the first for a bulk water crystal/liquid transition, were performed for 2944 waters in 54 replicas under pressure of 1 atm and T 0 = 330 K, and initially in perfect β ice configurations in symmetry SI, using the mW coarse-grained model [17] with periodic boundary conditions. Although β ice is never the thermodynamically stable state, the barrier to stable hexagonal α ice insures that it will not be sampled under these conditions and the metastable β ice-liquid transition is well defined in the restricted configuration space.…”
mentioning
confidence: 99%